Do constraints rather than freedom provide more opportunities for language learners? - Rai, Vishnu S (Journal of NELTA, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The paper reports the findings of a small scale research which tried to find out what happens when students do creative writing. Two tasks, one having more constraints and the other having more freedom were given to the learners. Interestingly it was found that the task which had more constraints was found to be more interesting to the learners. Key words: affective engagement, creative writing, experimental research DOI: 10.3126/nelta.v14i1.3098 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 119-131